Placenta accreta syndrome: an obstetrician’s nightmare - B., Sheetal; Shraddha; K., Arpitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Placenta accreta syndrome (PAS) poses significant clinical challenges during pregnancy and delivery, often resulting in severe maternal morbidity and mortality. This case series aims to present the varied presentations, management strategies, and clinical, and maternal outcomes associated with five patients diagnosed with PAS at our tertiary care center. A prospective analysis was conducted on five patients diagnosed with PAS who presented during the six months of study period. Demographics, clinical presentations, imaging findings, surgical interventions, and outcomes were systematically documented and analyzed. The case series included women aged 28 to 34 years, each with a history of caesarean deliveries. Common presentations included vaginal bleeding associated with placenta previa and varying degrees of placental invasion, namely accreta and percreta. All patients underwent planned caesarean deliveries, revealing severe placental adherence to surrounding structures, necessitating aggressive management. Significant postpartum hemorrhage occurred in all cases, with blood transfusions ranging from 3 to 6 units. Two patients required caesarean hysterectomy due to uncontrolled bleeding. All patients were admitted to the intensive care unit (ICU), with two cases resulting in mortality. Notable complications included post op infection, sepsis and bladder adhesion in individual cases, resulting in prolonged hospital stay for two patients. Histopathological confirmation supported the clinical diagnosis in all cases. PAS presents critical challenges in obstetric management, as demonstrated by the substantial morbidity and the requirement of multidisciplinary interventions in our case series. These findings underscore the importance of early diagnosis, thorough preoperative planning, and a collaborative approach to improve maternal outcomes in patients with PAS. Enhanced awareness and preparedness among healthcare providers are crucial to mitigate risks associated with this life-threatening condition. Further studies are warranted to refine management protocols and optimize patient outcomes in PAS.